Alister E. McGrath, Christianity: An Introduction. - Crotty, Robert (Journal for the academic study of religion, 2008)
Alister E. McGrath, Christianity: An Introduction. 2nd ed., Blackwell Publishing, Oxford and Melbourne, 2006, pp. xvi + 379, ISBN 1405109017 (hbk).